Results of an International Multidisciplinary Consultation on a New Criteria to Assess Acute Pancreatitis Severity: the “Determinant-Based Classification” - Uomo, Generoso; Bruno, Marco J; Dellinger, E Patchen; Forsmark, Christopher E; Layer, Peter; Lévy, Philippe; Poma, Enrique Maraví; Petrov, Maxim S; Shimosegawa, Tooru; Siriwardena, Ajith; et al. (JOP. Journal of the Pancreas, 2012)
Context The Atlanta definition of acute pancreatitis (AP) severity are based on empiric description of occurrences that are merely associated with severity, so resulting in a suboptimal assessment. Objective To develop a new classification of AP severity on the basis of a sound conceptual framework, comprehensive review of published evidence, and worldwide consultation. Methods Invitation to contribute to the development of a new classification of AP severity was sent to all surgeons, gastroenterologists, internists, intensivists, and radiologists who are currently active in the field of clinical AP. A global web-based survey was conducted and a dedicated international symposium was organized to bring contributors from different disciplines together and discuss the concept and definitions. Results The new classification of AP severity is based on the actual local and systemic determinants of severity. The “local determinants” relates to whether there is (peri)pancreatic necrosis or not, and if present whether it is sterile or infected. The “systemic determinants” relates to whether there is organ failure or not, and if present whether it is transient or persistent. The presence of a determinant can modify the effect of another such that the presence of both infected (peri)pancreatic necrosis and persistent organ failure has a greater effect on severity than either alone. The derivation of a classification based on the above principles results in four categories of severity: “mild”, “moderate”, “severe”, and “critical”. Conclusion This classification is the result of a consultative process amongst pancreatologists from 49 countries. It provides a set of concise up-to-date definitions of all the main entities pertinent to classifying the severity of AP in clinical practice and research. This ensures that the “Determinant-Based Classification” can be used in a uniform manner through the world.